SISTEM BERBASIS WEB, MANAJEMEN TRANSPORTASI, DIGITALISASI, TINJAUAN LITERATUR SISTEMATIS - Sahru Ramadhana; Sisil Damayanti; Andi Fajar Berlian; Putri Yunansi Bonsa; Imelda Masdar; Dhimas Tribuana (Jurnal Teknologi dan Bisnis Cerdas, 2025)
The transportation industry is undergoing a major transformation with the development of digital technology. Challenges such as complex fleet management, dynamic routes, high operational costs, and customer demand for fast service have driven the emergence of Web-Based Transportation Management Systems (WBTMS). This study conducted a Systematic Literature Review (SLR) to analyze various studies discussing the implementation of WBTMS in the transportation sector. The SLR process was conducted following the PRISMA guidelines, which include the stages of identification, screening, feasibility assessment, and final selection of studies. Literature was collected through several major databases such as Scopus, IEEE Xplore, ScienceDirect, and Google Scholar, with publications reviewed from 2020 to 2025. The purpose of this study was to identify trends, benefits, challenges, and existing research gaps. The review results indicate that WBTMS can improve operational efficiency, transparency, and customer service quality. However, major challenges remain in the aspects of IT infrastructure, integration with legacy systems, and human resource readiness. This study provides recommendations for the transportation industry and academia to strengthen strategies for adopting web-based systems in the future.